Passive cooling techniques - Du, Xiaoyu (A+BE | Architecture and the Built Environment, 2019)
Vernacular buildings are local buildings that have evolved overtime in one location to suit the local climate, culture and economy (Meir & Roaf, 2003). The construction of vernacular buildings uses locally available resources to address local needs. These kinds of structures evolve over time to reflect the environmental, cultural and historical context in which they exist (Coch, 1998). The building knowledge of this type of architecture is always handed down traditions and is thus more based on the knowledge achieved by trial and error and in this way handed down through the generations (Singh et al., 2009). Vernacular buildings are most often residential buildings. People have traditional lifestyles in vernacular buildings in virtually every climate in the world, from the Arctic circle to the tropics, in temperatures from below zero to over 40°C, and historically without the benefit of gas or electrically driven mechanized heating and cooling systems (Meir & Roaf, 2003). After the emergence of modernist architecture, aided by the industrial revolution, vernacular buildings are seen to be in a state of decline and are frequently looked down upon, abandoned, neglected or actively demolished. Associated, by many at least, with an out-dated past and poverty, they are steadily replaced by architectural models that favour more modern, inter-national technologies, materials and forms (Oliver, 1997). It is assumed, as in international standards such as CENASO 7730 or ASHRAE 55, that people suffer less discomfort in very closely controlled conditions, then such vernacular buildings, along with modern passive buildings, cannot provide their occupants with ‘comfortable’ indoor climates (Santamouris, 2007). But nowadays, by the more and more important issues of energy consumption in building construction sectors, the continuity of the vernacular traditions is emphasized in academic research and building practice because of its climate-response, passive model and low-energy consumption. The principles that were used in traditional buildings can very well be implemented in modern buildings so as to produce “energy saving” buildings. If these principles are sensibly adopted in modern buildings, it should be possible to build sustainable buildings for the future (Shanthi Priya, Sundarraja, Radhakrishnan, & Vijayalakshmi, 2012). We can learn a lesson from the approach of the builders who acknowledged the interdependence of human beings, buildings and physical environment (Coch, 1998). A “new vernacular” can be developed, harnessing the types of low-tech solutions that are familiar to most of us from the vernacular, together with modern passive and active renewable energy technologies and strategies to reflect the new cultural, climatic and economic realities of the 21st century (Meir & Roaf, 2003). Vernacular buildings have to adapt to the environment through low-tech methods. Changing building form and material is the most important technique to adapt to the environment to obtain the best comfortable living space, in another words, the environment deeply influenced building form design and material use. Fathy (1986) described the climate effect on building form generation in vernacular building as: “For example, the proportion of window to wall area becomes less as one moves toward the equator. In warm areas, people shun the glare and heat of the sun, as demonstrated by the decreasing size of the windows. In the subtropical and tropical zones, more distinctive changes in architectural form occur to meet the problems caused by excessive heat. In Egypt, Iraq, India, and Pakijstan, deep loggias, projecting balconies, and overhangs casting long shadows on the walls of buildings are found. Wooden or marble lattices fill large openings to subdue the glare of the sun while permitting the breeze to pass through. Such arrangements characterize the architecture of hot zones, and evoke comfort as well as aesthetic satisfaction with the visible endeavour of man to protect himself against the excessive heat”. In recent years, a significant amount of research has looked specifically at environmental performance issues of vernacular architecture, including its thermal properties, energy consumption and resources (Foruzanmehr & Vellinga, 2011). Both qualitative and quantitative such as field measurements, field surveys, statistical methods, comparative study and computer simulation methods are used in the investigation of the performance of vernacular buildings. Professor Paul Oliver of Oxford University compiled the book “Dwellings: Encyclopedia of Vernacular Architecture” and published in 1997 with 4000 pages collection of research by over 750 authors from 80 countries. With two volumes categorized by climate and the ‘‘vernacular responses’’ of a plethora of cultures and another volume focused on materials, resources and production, it is the world’s foremost source for research in the area (Zhai & Previtali, 2010). Zhai and Previtali (2010) introduced an approach to categorizing distinct vernacular regions and evaluate energy performance of ancient vernacular homes as well as identify optimal constructions using vernacular building techniques. Chandel, Sharma, and Marwah (2016) reviewed the vernacular architecture features affecting indoor thermal comfort conditions and energy efficiency for adaptation in modern architecture to suit present day lifestyles. Singh et al. (2009) carried out a qualitative analysis on the vernacular buildings in north-east India. And Shanthi Priya et al. (2012) have conducted the qualitative and quantitative analysis to investigate the indoor environmental condition of a vernacular residential building in coastal region of Nagapatinam, India. Cardinale, Rospi, and Stefanizzi (2013) performed one experimental research on two types of vernacular buildings which lie in Southern Italy. Nguyen, Tran, Tran, and Reiter (2011) carried out an investigation on climate responsive design strategies of vernacular housing in Vietnam by a new research methodology which is adapted to the natural and social context of Vietnam. Ng and Lin (2012) analysed the microclimate of two Minangkabau vernacular houses in villages of Balimbing of Bukittinggi, Sumatra, Indonesia. Ali-Toudert, Djenane, Bensalem, and Mayer (2005) addressed the issue of outdoor thermal comfort in a hot and dry climate in relation to urban geometry. Beccali, Strazzeri, Germanà, Melluso, and Galatioto (2017) reviewed some models evaluating thermal comfort in natural ventilated vernacular buildings, based on adaptive approaches. Borong et al. (2004) concluded that sun shading and insulation are of great importance while natural ventilation is just considered as an auxiliary approach for the design principles of the traditional Chinese vernacular dwellings, based on the field measurements of the thermal environment parameters and a long-term auto-recorder of the indoor and outdoor temperature at four typical traditional vernacular dwellings at Wannan area in summer. Bouillot (2008) studied six Chinese vernacular houses in different provinces and found that the value and the diversity of the Chinese housing stock is due to the combination of the specific structure of the Chinese eastern climates, which creates the contrast of cold-dry winters and hothumid summers, with the structure of the Ming t’ang, which contains the opposition of the yin and the yang. Liu et al. (2011)’s study interprets the characteristic of warm in winter and cool in summer in traditional Yaodong dwelling by measuring the indoor, outdoor and the wall’s temperatures in winter and summer. The results show that the Yaodong thick wall effectively damps the external temperature wave and keeps a steady inner surface temperature, are the chief causes of warm in winter and cool in summer in Yaodong. Gou et al. (2015) focused on a qualitative analysis of ancient dwellings located in the village of Xinye, in the hot summer and cold winter region of China. According to the analysis, the climate responsive strategies of the dwellings are mainly focused on natural ventilation, sun-shading and thermal insulation, illustrated by different building aspects such as the building location, building group layout and orientation, internal space arrangement, opening design, among other variables. Soflaei, Shokouhian, and Zhu (2017) investigated the potential of traditional courtyard houses in Iran and China in responding to environmental challenges alongside social norms over a long period of time. The social and environmental dimensions of the sustainability as well as the main elements of traditional courtyard houses in Iran and China were identified. Because of the advantage of vernacular building using passive ways to achieve thermal comfort and energy efficiency as mentioned above, this research will start with the investigation of a Chinese vernacular buildings in chapter 4. The next part of the literature review is an overview of passive cooling techniques.